2022
DOI: 10.5812/ijpr-127028
|View full text |Cite
|
Sign up to set email alerts
|

New Cytotoxic Premyrsinane-Type Diterpenes from Euphorbia aleppica Against Breast Cancer Cells

Abstract: : Euphorbia is used in traditional medicine to remove warts, possibly due to its cytotoxic or antiviral effects. This study investigated its phytochemistry and bioactive compounds. Euphorbia aleppica from the Euphorbiaceae family was collected from Kuhdasht, Lorestan, Iran. Plant material was dried and ground. Extraction was performed by maceration using a dichloromethane-acetone solvent. After removing fatty contents, fractionation was done by open column chromatography. Based on the initial H-NMR spectra, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Former studies concerning the evaluation of cytotoxicity and possible therapeutic application of diterpenoids in breast cancer treatment have also revealed valuable results as well. In an identical study on Euphorbia aleppica , two new cytotoxic premyrsinane diterpenes were introduced and assessed for their anti-cancer effects on MCF-7 and MDA-MB-231 cell lines which determined their probable potency [ 16 ]. Similarly, another investigation on cyclomyrsinane diterpenes from Euphorbia species proved the potential activity of compounds that had structural similarities to the ones elucidated in the present research against the same breast tumor cell lines [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Former studies concerning the evaluation of cytotoxicity and possible therapeutic application of diterpenoids in breast cancer treatment have also revealed valuable results as well. In an identical study on Euphorbia aleppica , two new cytotoxic premyrsinane diterpenes were introduced and assessed for their anti-cancer effects on MCF-7 and MDA-MB-231 cell lines which determined their probable potency [ 16 ]. Similarly, another investigation on cyclomyrsinane diterpenes from Euphorbia species proved the potential activity of compounds that had structural similarities to the ones elucidated in the present research against the same breast tumor cell lines [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have chemotaxonomic significance and were isolated only from Euphorbia species, including E. prolifera [ 6 , 7 ], E. sogdiana [ 8 ], E. dracunculoides [ 9 , 10 ], E. lathyris [ 11 ] E. sanctae-catharinae [ 12 ], E. macroclada [ 13 ], E. falcata [ 14 , 15 ], and E. aleppica [ 16 ] with antifungal effects against plant pathogenic fungi, cytotoxic activities, and modulating the drug resistance in cancer cells [ 7 , 8 , 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…The next step is generally a liquid–liquid partition process, where n -hexane or petroleum ether are usually used to defat the extract, followed by a partition with ethyl acetate (EtOAc) and water or mixtures with acetonitrile in order to concentrate the diterpenic compounds in the organic phase. Depending on the extraction solvents and the amount of the crude extract, other techniques could also be used, including vacuum liquid chromatography over RP-18 silica gel or poliamide to remove fats, hydrophilic compounds, and chlorophylls [ 52 , 53 , 54 , 55 ]. The EtOAc or acetonitrile crude fraction previously obtained is further fractionated through a combination of different chromatographic techniques, with column chromatography over silica-gel being the first to be carried out.…”
Section: Phytochemistrymentioning
confidence: 99%
“…A study of new cytotoxic diterpenes of the premysinane type from E. aleppica L. was conducted by Zolfaghari et al [ 53 ]. A new compound 153 and a previously isolated compound 154 [ 94 ] ( Figure 19 ) were tested against MCF-7 and MDA-MB 231 breast cancer cells.…”
Section: Distribution Diversity and Biological Activities Of Myrsinan...mentioning
confidence: 99%
“…Studies of the biological activities of premyrsinanes are scarce in the literature; this is likely because of the reduced amount of the isolated compounds [ 10 ]. Nevertheless, several studies have reported that premyrsinanes possess promising anticancer [ 17 , 18 , 19 ], multidrug resistance reversal [ 20 ], and anti-inflammatory activities, inhibiting the lipopolysaccharide-induced NO production [ 21 ]. Furthermore, their potential biosynthetic precursors, euphoboetirane A ( 3 ) and epoxyboetirane A ( 4 ), have demonstrated a promising activity as promoters of neural stem cells (NSC) proliferation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%